The modernist nation : generation, renaissance, and twentieth-century American literature - Soto, Michael (University of Alabama Press, 2004)
"Soto is a clever and convincing reader of modernist prose and makes a fair case for the value of the generational model. [His book] beats notions of 'ages' or 'epochs', because it is organic and bridges individual and collective historiography, while also allowing for the non-contemporaneity of the contemporaneous, the coexistence of multiple generations in time and space."--Modern Language Review "[The Modernist Nation's] historical span is impressive, ranging from Ralph Waldo Emerson to James Baldwin. ... One of Soto's contributions is to continue the work of thinking